2023
DOI: 10.1037/adb0000886
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative examination of positive and negative consequences young adults experience from simultaneous alcohol and cannabis use.

Abstract: Objective: Alcohol and cannabis are two of the most commonly used substances among young adults, and most individuals who use both substances use them simultaneously, that is, on the same occasion such that their effects overlap. Given the high prevalence of simultaneous alcohol and cannabis use, it is important to understand the relationship between simultaneous use and consequences. This study presents a qualitative examination of positive and negative consequences of simultaneous use. Method: We conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…Qualitative approaches would allow for the inclusion of negative and positive consequences that may be unique to or particularly relevant for SAM use, such as those outlined by Boyle et al. (2023; e.g., feeling nauseated after a particular order of use). More research is needed to develop a comprehensive consequences measure specific to SAM use that can capture its unique characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Qualitative approaches would allow for the inclusion of negative and positive consequences that may be unique to or particularly relevant for SAM use, such as those outlined by Boyle et al. (2023; e.g., feeling nauseated after a particular order of use). More research is needed to develop a comprehensive consequences measure specific to SAM use that can capture its unique characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Boyle et al. (2023) conducted a qualitative examination of young adults and found that there were specific positive consequences of SAM use that were different from single substance use consequences. For example, participants reported that SAM use improved preexisting relationships.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Items were summed to create a total score for number of negative and number of positive consequences experienced on a simultaneous use day. Items were derived from several measures including the Brief Young Adult Alcohol Consequences Questionnaire (Kahler et al, 2005), the Marijuana Problems Scale (Stephens et al, 2000), the Positive Drinking Consequences Questionnaire (Corbin et al, 2008), Marijuana Motives Questionnaire (Lee et al, 2009), Motives for Simultaneous Alcohol and Marijuana Use (Patrick et al, 2018), the Daily Alcohol-Related Consequences and Evaluations for Young Adults Measure (Lee, Cronce, et al, 2017), the Acute Hangover Scale (Rohsenow et al, 2007), and our formative qualitative work (Boyle, Singh, Lopez, Carey, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%